Elevated core-fucosylated IgG is a new marker for hepatitis B virus-related hepatocellular carcinoma - Yi, Chang-Hong; Weng, Honglei; Liebe, Roman; Dooley, Steven (OncoImmunology, 2015)
Immunoglubulin G (IgG) and its abnormal glycosylations are associated with carcinogenesis. The present study investigates the relationship between cancer-derived IgG and clinicopathological characteristics in hepatocellular carcinoma (HCC) and assesses the value of serum N-glycosylated IgG in diagnosing and monitoring hepatitis B virus (HBV)-related HCC. Tissue microarray analysis of 90 HCC tissues showed that HCC patients with IgG immunopositivity had higher levels of core-fucosylated α fetoprotein (AFP-L3), larger tumors, and a higher incidence of portal vein tumor thrombus. HCC-derived IgG stimulated the growth of liver cancer cells in vitro. HCC patients presented a significantly increased fraction of Lens culinaris agglutinin binding IgG (core-fucosylated IgG, IgG-L3) among total serum IgG. The clinical diagnostic performance of serum IgG-L3% was evaluated in 3 case-control studies (1 training set and 2 validation cohorts), including 293 patients with HCC, 131 with liver cirrhosis, 132 HBV carriers, and 151 healthy controls. IgG-L3% had better general diagnostic performance than AFP in the training set and validation cohort 1 (accuracy: 81.33-85.11% versus 63.33-78.61%). In validation cohort 2, where we aimed to assess the efficiency of IgG-L3% in patients with AFP-negative HCC, the diagnostic accuracy of IgG-L3% was 72.54-73.60%. Finally, a longitudinal evaluation based on 31 HCC patients demonstrated that IgG-L3% decreased in 24 patients after curative surgery. The remaining 7 patients showed elevated IgG-L3% and post-operative recurrence. HCC patients with higher IgG-L3% had poor survival during a 3-year follow up. We conclude that HCC-derived IgG is correlated with progressive behavior of HCC. Therefore, elevated core-fucosylated IgG is a new diagnostic and prognostic marker in HBV-related HCC.